Demographic Predictors of Routine Immunization and Vaccines Services Acceptance Among Childbearing Mothers in Bauchi State, Nigeria - Inah, Yakubu A.; Nenlat, Raphael R. (International Journal of Human Kinetics, Health and Education, 2023)
This study investigated demographic predictors of routine immunization and vaccines services acceptance among childbearing mothers (CBMs) in Bauchi State. Two specific objectives and, two corresponding research questions and one null hypothesis were formulated for the study. The cross-sectional survey design was used for the study. The population for the study comprised of all childbearing mothers in Bauchi State (3,221,528). Multi-stage sampling procedure was adopted to select a sample size of 800 childbearing mothers (CBM). A structured Demographic Predictor of Routine Immunization and Vaccines Services Acceptance Questionnaire (DPRIVSAQ) was used for data collection. Frequency counts and Percentages were used to answer the research questions while the null hypothesis was tested using Binary logistic regression model at .05 level of significance. The findings showed that CBMs had high level of acceptance of immunization vaccines (70.3%) and routine immunization services schedules (65.1%) in Bauchi State. Tertiary education (OR=0.35 [0.19—0.65], p<.05) and secondary education (OR=0.44 [0.24 – 0.81] p<.05) were significant predictors of acceptance of routine immunization and vaccines services among CBMs in Bauchi State. This implies that attaining a tertiary and secondary level of education were less likely to predict acceptance of immunization vaccines among CBMs, while attaining a secondary education was less likely to predict acceptance of routine immunization. It was therefore recommended that there is need for continuous maternal education programmes in order to reinforce and sustain the high and moderate levels of acceptance of routine immunization and vaccine services among CBMs in the state.